ANALISIS KUALITAS PELAYANAN DI PT. PLN (PERSERO) REGIONAL JATENG & DIY (Indeks Kepuasan Masyarakat Wilayah Kerja UPJ Semarang Selatan) - Permatasari, Charolina Ayu; Sulandari, Susi; Fathurrohman, Fathurrohman (Journal of Public Policy and Management Review, 2015)
PT. PLN (Persero) Regional Central Java and Yogyakarta Network Services Unit South of Semarang is an institution which runs services in the field of electrical energy. This study aimed to analyze the performance of services and satisfaction user service provided by PT. PLN (Persero) based on community satisfaction index. This research was conducted on the basis of KEP. MENPAN No.25/2014 on the concept of excellent service or the quality of public services. In which there are fourteen indicator services performance of community satisfaction which assesses the performance of services.. This study uses a quantitative descriptive analytical approach as the unit of analysis, while the data collection techniques obtained through questionnaires, documentation, and observation. These results of public satisfaction index value performance of services carried out by PT. PLN (Persero) Regional Central Java and Yogyakarta UPJ South Semarang by 72, including the Good category. PT.PLN service user satisfaction (Persero) degree of conformity between performance and expectations reached 89.84% belong to the category is not satisfied because the performance is lower than the expectations of customers The conclusion that can be derived that the performance of services by PT. PLN (Persero) Regional Central Java and Yogyakarta UPJ South Semarang categorized as good with community satisfaction index score of 72. However, there needs to be improvement in four indicators in quadrant A is based on Cartesian diagram, include: Procedures of service, discipline of service personnel, service requirements, and speed services.